Renal Sensory Activity Regulates the γ-Aminobutyric Acidergic Inputs to the Paraventricular Nucleus of the Hypothalamus in Goldblatt Hypertension - Milanez, Maycon I. O.; Veiga, Amanda C.; Martins, Beatriz S.; Pontes, Roberto B.; Bergamaschi, Cassia T.; Campos, Ruy R.; Nishi, Erika E. (Frontiers in Physiology, 2020)
Renal sensory activity is centrally integrated within brain nuclei involved in the control of cardiovascular function, suggesting that renal afferents regulate basal and reflex sympathetic vasomotor activity. Evidence has shown that renal deafferentation (DAx) evokes a hypotensive and sympathoinhibitory effect in experimental models of cardiovascular diseases; however, the underlying mechanisms involved in this phenomenon need to be clarified, especially those related to central aspects. We aimed to investigate the role of renal afferents in the control of γ-aminobutyric acid (GABA)ergic inputs to the paraventricular nucleus (PVN) of the hypothalamus in renovascular hypertensive (2K1C) rats and their influence in the regulation of cardiovascular function. Hypertension was induced by clipping the left renal artery. After 4 weeks, renal DAx was performed by exposing the left renal nerve to a 33 mM capsaicin solution for 15 min. After 2 weeks of DAx, microinjection of muscimol into the PVN was performed in order to evaluate the influence of GABAergic activity in the PVN and its contribution to the control of renal sympathetic nerve activity (rSNA) and blood pressure (BP). Muscimol microinjected into the PVN triggered a higher drop in BP and rSNA in the 2K1C rats and renal DAx mitigated these responses. These results suggest that renal afferents are involved in the GABAergic changes found in the PVN of 2K1C rats. Although the functional significance of this phenomenon needs to be clarified, it is reasonable to speculate that GABAergic alterations occur to mitigate microglia activation-induced sympathoexcitation in the PVN of 2K1C rats.